Effect Of Vitamin-Mineral Supplemented Diet And Feeding Strategies On Reproductive Performance Of Labeo Rohita Broodstock (Applied Biological Research, 2016)
The present study was conducted to assess the effect of vitamin-mineral  supplemented diet and feeding strategies on reproductive performance  of fish (Labeo rohita). Two diets, with and without vitamin-mineral  mixture supplementation, were fed to Labeo rohita yearlings for a period  of 8 months (April-November) at two feeding rates i.e. 3 and 4% b.w.  and two feeding frequencies i.e. once and twice day-1. The study revealed  that ganado-somatic index and relative fecundity were significantly  higher in diet supplemented with vitamin-mineral mixture @ 4% b.w.  fed twice a day during both pre-spawning (July) and post-spawning i.e.  at resorption (September). Absolute fecundity and ova diameter were  equally higher in control and treatment diets supplemented @ 4% b.w.  twice day-1. The study suggests that supplementation of vitamin-mineral  mixtureat higher feeding rate and frequency improves reproductive  potential of Labeo rohita broodstock.
Keywords: Fecundity; feeding strategies; gonado-somatic index; Labeo rohita; vitamin-mineral supplementation